Clinical experience of thyroglossal cyst management - Naveen Kumar, A. G. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Thyroglossal cyst is a cystic swelling arising from embryological remnant of thyroglossal cyst. Cyst is typically located in the midline of the anterior neck and moves upward with tongue protrusion. The gold standard management for thyroglossal cyst is the Sistrunk procedure. Methods: Total of 32 patients of all ages and both sexes operated at Sapthagiri Institute of Medical Science and Research Centre, Bangalore during the study duration were included a detailed history and thorough physical examination was done to arrive clinical diagnosis. Ultrasound studies and FNAC were done in all cases to confirm the clinical diagnosis of thyroglossal cyst. Management was mainly surgical and Sistrunk operation was done in all cases. Results: Thirty two patients of with the diagnosis of thyroglossal cyst were managed from 2011 to 2018 in the department of ENT, Sapthagiri Institute of Medical Science, Bangalore, 20 (62.5%) were females and 12 (37.5%) were males age ranged from 5 to 40 years; mean age was 16.5 years. Conclusions: Thyroglossal cyst presents most commonly in paediatric age as cystic painless midline neck swelling. Diagnosis is made on clinical examination complimented with ultrasound and FNAC. Sistrunk operation is the treatment of choice to prevent recurrence and histopathological examination of the surgical specimen is must to rule out malignant transformation in the cyst.